CRITICAL ANALYSIS OF ELECTORNIC BANKING IN NIGERIA - Nnabuihe, Nwachukwu Sunny; Stanley, Nwaneri; Ngozi, Ogbuehi (European Scientific Journal, ESJ, 2015)
The recent evolvement in technology in the banking industry is enormous. Electronic banking has improved banking in the areas of customer service delivery and quicker and effective data capturing. At least it has reduced some hardship in accessing information. Banking has left manual operation of the past but its innovations and service operatives have recorded enormous failures in quality services and security of products. Government should improve her economy as this system of banking will not survive in a weak economy. The researcher intends to access the relevance of information technology in the banking industry act to access the quality of services delivery in the recent past.